PASS+: A NEW WAY OF SAVING LIVES - Fonseca, Kevin Diogenes; Ribeiro, Guilherme Francisco Alves; Rodrigues, João Arthur Gonà§alves; Antunes, Gustavo Henrique Couto; Costa, João Armandes Vieira; Costa Filho, Antà´nio Martins; Anjos, Arthur Augustinho dos (CIPEEX, 2022)
ONE OF THE MOST UNFORTUNATE SITUATIONS IN BRAZILIAN HEALTH IS FOUND IN QUEUES AT HEALTH CENTRES, WHERE PEOPLE OFTEN SPEND A CONSIDERABLE TIME OF THEIR DAYS IN QUEUES WAITING TO BE ATTENDED TO. IN ORDER TO SOFTEN THIS PROBLEM AND GUARANTEE MORE FREE TIME FOR PEOPLE WHO EXPECT TO BE SEEN AT CLINICS AND HEALTH POSTS, WE STARTED THE PRODUCTION OF THE PASS+. IN MAKING THE IDEA FOR THIS APPLICATION, WE USED THE BEST SOFTWARE ENGINEERING PRACTICES FOR PROJECT MANAGEMENT AND REQUIREMENTS CREATION, RESPECTIVELY SUPPORTED BY SCRUMBAN (A COMBINATION OF THE ORGANIZATIONAL FRAMEWORKS "SCRUM" AND "KANBAN") AND LEAN INCEPTION, DEFINING THAT THE APPLICATION WILL HAVE SUPPORT FOR IOS AND ANDROID, LATER HAVING A WEB VERSION. IN ADDITION TO DEFINING THAT THE APPLICATION WILL BE A SIMPLE WAY OF NOTIFYING THE CUSTOMER ABOUT AN APPOINTMENT AND WILL FACILITATE THE APPOINTMENT SCHEDULING PROCESS, LEAN INCEPTION ALSO FACILITATED THE PROCESS OF DEFINITION OF NON-FUNCTIONAL REQUIREMENTS, SUCH AS ISSUES RELATED TO ACCESSIBILITY, WHICH WILL BE A KEY POINT IN THE CREATION OF THIS PROJECT, AS IT IS AN APPLICATION THAT WILL BE AVAILABLE FOR ALL AGES. IN ADDITION, WE CAN ALSO MENTION FIGMA, WHICH IS A GREAT ALLY IN THE DESIGN AND PROTOTYPING PROCESS, HELPING TO VALIDATE WHAT MUST BE IN THE APP AND HOW IT WILL BE IMPLEMENTED. FINALLY, IT CAN BE SAID THAT IN THE CURRENT PHASE OF THE PROJECT, WE ARE IN THE PROTOTYPE VALIDATION PERIOD IN FIGMA, WHICH IS ALREADY DYNAMIC AND USABLE, WITH THE PROSPECT THAT IN THE NEXT SPRINT (IMPLEMENTATION CYCLE OF ONE OR MORE FUNCTIONALITIES WITHIN THE SCRUM MODEL) WE WILL START CODING THE PROJECT. KEYWORDS: QUEUES, REDUCTION, HEALTH, ACCESSIBILITY